The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4103/aian.aian_171_21
|View full text |Cite
|
Sign up to set email alerts
|

Wilson's Disease Update

Abstract: Wilson's disease (WD) is an autosomal recessive disorder due to ATP7B gene mutation, resulting in defective copper metabolism, with the liver and brain being primarily affected. WD being a treatable disorder, early diagnosis and proper management may result in near complete recovery. It has received significant attention over the past 50 years, with several Indian contributions. This study collates published Indian studies on WD in Pubmed and Embase databases and puts them in perspective. Several Indian case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
(131 reference statements)
0
9
0
1
Order By: Relevance
“…On the other hand, the mechanism was not established and rarely reported in clinical treatment [ 52 ]. A recent study showed Wilson’s disease-related treatment [ 53 , 54 ] and lead poisoning recovery [ 55 ]. Interestingly, this study showed that DPA preserved the beating of EBs ( Figure 4 A) but failed to restore the impairment at the morphology ( Figure 4 B) and gene level ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the mechanism was not established and rarely reported in clinical treatment [ 52 ]. A recent study showed Wilson’s disease-related treatment [ 53 , 54 ] and lead poisoning recovery [ 55 ]. Interestingly, this study showed that DPA preserved the beating of EBs ( Figure 4 A) but failed to restore the impairment at the morphology ( Figure 4 B) and gene level ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Еще одной страной с высоким числом больных считают Индию. Среди расстройств гепатобилиарного тракта в Северной Индии БВ составляет 7,6% [12]. Связывают данный факт с относительной изоляцией людей на островах и с высокими показателями смешанных браков.…”
Section: Discussionunclassified
“…Approximately 10% of patients with WD have a psychiatric presentation [116] ranging from a decline in school performance to an affective disorder, personality change, irritability, psychosis and others; in such patients, the diagnosis of WD may not be considered. In addition to hepatic and neuropsychiatric manifestations, there is a long list of other systemic effects of WD affecting the skeleton, heart, RBCs (hemolytic anemia), kidneys and skin [117].…”
Section: Wilson's Diseasementioning
confidence: 99%
“…The midbrain "face of the giant panda" was present in 12%, and less commonly was central pontine myelinolysis and the bright claustrum sign. The pontine equivalent of the face of the giant panda is the "face of the miniature panda" [117]. When the diagnosis remains in question, a liver biopsy with measurement of copper can be performed.…”
Section: Wilson's Diseasementioning
confidence: 99%